Bilingual teaching practices in South African higher education : making a case for terminology planning - Mawonga, Sisonke (Rhodes University, Faculty of Humanities, School of Languages, 2015)
When the apartheid government was in power universities in South Africa were segregated according to a race and language. After apartheid, the democratic government came into power and its vision was abolition of segregation. There was also equal and equity of access to public institutions which were set aside for certain people to have access to. Access to universities was equalized and students with different racial, social, cultural and linguistic backgrounds were allowed access to universities which they used not to have access to before. The students"Ÿ access to all universities led to diversity within these institutions. Even though this was the case, there were no changes in the system prevalent during apartheid. English, for example, continued to be the language of learning and teaching (LoLT) while the numbers of students who speak languages other than English (LOTE) as home languages was also increasing. The Constitution of South Africa (Section 6, Act 108 of 1996) acknowledges the previous marginalization of indigenous languages in the country and encourages the development and use of these languages as official languages. The right of access to educational institutions, and accessing education in one"Ÿs language, if that language is one of the official languages, is also encouraged by the Constitution. There are other supporting legislative documents such as the Languages Bill (2011), the Higher Education Act (1997) and the national Language Policy for Higher Education (LPHE) (2002) that support multilingualism, the equal promotion of the official languages as well as use of multiple languages in higher education institutions (HEIs) to support learning. The above mentioned policies and legislations may exist to ensure equality and equity, and even though HEIs have become heterogonous, that does not guarantee that the students enrolled in these institutions have equal access to knowledge offered by the HEIs in SA. This research uses the theories of languages and conceptualization; language and learning as well as language planning to show that the students"Ÿ first languages in learning can assist to facilitate cognition. Terminology development, as part of corpus planning which is the body of language planning is introduced in this study in the form of bilingual glossaries as an intervention especially for students"Ÿ whose mother tongue is not English as language used for learning at university for different disciplines tend to be abstract. The data for this research was collected from the 2014 first year students registered in the Extended Studies Unit (ESU) in the Humanities Faculty at Rhodes University. Research methods such as questionnaires, participant observations, interviews as well as content analysis were used to collect the data. These methods were used to look at the students"Ÿ use and perceptions of bilingual glossaries as additional resource materials which can assist them in learning. A Political Philosophy I module offered by the Political Science department was used for this research. This thesis presents a model which can be used for the development of bilingual glossaries in order to facilitate learning. The thesis recommends the use of corpus extraction tools such as WordSmith Tools (WST) that can be used to generate and extract terms and illustrates the use of this tool by extracting terms from an English Political Philosophy textbook. These terms are defined and these are then translated into isiXhosa to provide a sample of the bilingual glossary. This glossary has been designed to illustrate how the bi/multilingual glossaries with terms and definitions can be developed in order for use by students to facilitate learning them. The study also presents a terminology list which consists of Political Philosophy terms that have been generated during the corpus extraction process. It is recommended that further research looks into the development of bi/multilingual glossaries using the suggested model so that the students who are speakers of LOTE can also be able to understand abstract terms which are used at university
Keywords: Language and education -- South Africa; Native language and education; Language policy -- South Africa